UBE2D1 RNA Expression Was an Independent Unfavorable Prognostic Indicator in Lung Adenocarcinoma, but Not in Lung Squamous Cell Carcinoma. (21st October 2018) - Hou, Liyan; Li, Yingbo; Wang, Ying; Xu, Dongqiang; Cui, Hailing; Xu, Xiaoyan; Cong, Ying; Yu, Chengyong
Abstract : In this study, we investigated the potential prognostic value of ubiquitin-conjugating enzyme E2D1 ( UBE2D1 ) RNA expression in different histological subtypes of non-small-cell lung cancer (NSCLC). A retrospective study was performed by using molecular, clinicopathological, and survival data in the Cancer Genome Atlas (TCGA)—Lung Cancer. Results showed that both lung adenocarcinoma (LUAD) (N = 514 ) and lung squamous cell carcinoma (LUSC) (N = 502 ) tissues had significantly elevated UBE2D1 RNA expression compared to the normal tissues (p < 0.001 andp = 0.036, respectively). UBE2D1 RNA expression was significantly higher in LUAD than in LUSC tissues. Increased UBE2D1 RNA expression was independently associated with shorter OS (HR: 1.359, 95% CI: 1.031–1.791, p = 0.029 ) and RFS (HR: 1.842, 95% CI: 1.353–2.508, p < 0.001 ) in LUAD patients, but not in LUSC patients. DNA amplification was common in LUAD patients (88/551, 16.0%) and was associated with significantly upregulated UBE2D1 RNA expression. Based on these findings, we infer that UBE2D1 RNA expression might only serve as an independent prognostic indicator of unfavorable OS and RFS in LUAD, but not in LUSC.